EFFECT OF PRE-DRYING, CEFOTAXIME AND SEASON ON XIME AND SEASON ON XIME AND SEASON ON IN VITRO CULTURE ESTABLISHMENT IN BANANA CV. KAMALAPUR RED (AAA) - D. P. PRAKASHA , G.RAMAYA , GAJANANA KUSTAGI AND K. N. KATTIMNI (The Bioscan, 2018)
The present study was conducted for finding out factors affecting in vitro establishment of clean cultures in banana Cv. Kamlapur red. Healthy sword suckers were sterilized using sodium hypochlorite and mercuric chloride with a standardized protocol for culture initiation. The MS medium with 30gmL- sucrose, 8gmL- agar and 3mgL- BAP was used as culture medium. In the experiment on pre-drying of suckers under shade for 1-6 days after removal from the field, suckers pre-dried for five days showed significantly less contamination with highest clean cultures (76.40%), whereas without pre-drying showed more contamination and lowest clean cultures (43.17%). In the experiment conducted on effect of season of sucker collection, contamination was significantly less in suckers collected during summer season (63.40%) and however, suckers collected during winter were found to be best to dissect during culture initiation (60.45%). In the experiment on immersion of sucker in cefotaxime of 100-600mgL- of water for 15 minutes, suckers treated with 400 mgL- cefotaxime for 15 minutes showed significantly less contamination with establishment of highest clean cultures (85.62%). Suckers treated with both increased or reduced cefotaxime was not beneficial. The results of the present study are useful in obtaining clean cultures for mass multiplication.